Nanoparticle/DNAzyme Based Biosensors for Heavy-Metal Ion Detection: Effect of DNAzyme Surface Modifications on Device Sensitivity - Evangelos Aslanidis; Evengelos Skotadis; Chryssi Panagopoulou; Annita Rapesi; Georgia Tzourmana; George Tsekenis; Dimitris Tsoukalas (Engineering Proceedings, 2023)
In this work, a biosensor for heavy metal-ion detection, based on platinum nanoparticles (Pt NPs) and DNAzymes, is presented. Two chemical modification groups were utilized for the DNAzymes’ immobilization on the Pt NPs film. The biosensors were characterized concerning their ability to detect Lead (Pb2+) ions in buffer solutions. Both immobilization techniques exhibit great sensitivity with a detection limit of 25 nM.